2019
DOI: 10.3389/fphys.2019.01221
|View full text |Cite
|
Sign up to set email alerts
|

Effect of L-Arginine on Titin Expression in Rat Soleus Muscle After Hindlimb Unloading

Abstract: Nitric oxide (NO), produced by NO-synthases via L-arginine oxidation, is an essential trigger for signaling processes involved in structural and metabolic changes in muscle fibers. Recently, it was shown that L-arginine administration prevented the decrease in levels of the muscle cytoskeletal proteins, desmin and dystrophin, in rat soleus muscle after 14 days of hindlimb unloading. Therefore, in this study, we investigated the effect of L-arginine administration on the degree of atrophy changes in the rat sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 54 publications
(78 reference statements)
6
13
0
Order By: Relevance
“…A previous study has shown that the skeletal muscle atrophy starts during short-term unloading (at 2–4 days) [ 18 ] and that the SOL muscle atrophied to nearly half its original size in about 2 weeks [ 19 ]. Although a recent study indicated that 7 days of hind limb suspension was enough to reduce the SOL muscle weight in Wistar rats, the contraction and weight of EDL muscle were not measured [ 20 ]. The TS fixation method was simple because it involved the suspension of the tail only, whereas previous studies immobilized hind limbs by applying a cast [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that the skeletal muscle atrophy starts during short-term unloading (at 2–4 days) [ 18 ] and that the SOL muscle atrophied to nearly half its original size in about 2 weeks [ 19 ]. Although a recent study indicated that 7 days of hind limb suspension was enough to reduce the SOL muscle weight in Wistar rats, the contraction and weight of EDL muscle were not measured [ 20 ]. The TS fixation method was simple because it involved the suspension of the tail only, whereas previous studies immobilized hind limbs by applying a cast [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are indirect data testifying that hyperphosphorylation of skeletal muscle titin enhances its sensitivity to cleavage by calpains (for references, see Ref. 55 ). Our data obtained in this work do not contradict this assumption.…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional support prevents muscle breakdown in the chronic phase [ 116 ]. Regarding titin, Ulanova et al reported that L-arginine administration decreased the loss of titin in rat soleus muscle [ 117 ]. Since nutritional support team involvement can improve calorie and protein delivery [ 118 , 119 ], a multidisciplinary team intervention is expected to be important in PICS if urinary titin is elevated in patients.…”
Section: Picsmentioning
confidence: 99%